The Effects of Soil Solarization and Compost on Soil Suppressiveness against Fusarium Oxysporum f. sp. Melonis. Issue 3 (3rd July 2017) - Kanaan, Housam; Medina, Shlomit; Raviv, Michael
ABSTRACT: Soil suppressiveness against Fusarium was tested using solarized and non-solarized soils combined with composts of three maturation levels, and a non-amended control. The soils were sampled on three dates: after previous year solarization but before current year solarization (0 weeks), at the end of the solarization period of the current year (4 weeks), and 4 weeks later (recovery time). Melon seedlings were inoculated with Fusarium spores and disease severity was assessed. The study showed a reduction of soil suppressiveness capacity against Fusarium oxysporum f. sp. melonis after 1 year of solarization (0 weeks). Fusarium disease severity in artificially inoculated melon plants, expressed by area under the disease progress curve, was higher in solarized soil than in non-solarized soil. Compost addition lowered the disease severity, both in the solarized and in the non-solarized soils. However, suppression was not obtained at the end of the solarization period, whereas compost beneficial effect was found at this time.